Controlled SLN Delivery by ThermoresponsiveIn-situ Forming Erodible Gels; A Whole-body and Organ Imaging Study - Dorraj, Golnar; Dadashzadeh, Simin; Erfan, Mohammad; Moghimi, Hamid R. (Current Drug Delivery, 2018)
Background: Nanoparticles (NPs) suffer from rapid clearance from body and require frequent dosing if long treatment is required. Method: In order to solve this problem for solid lipid nanoparticles (SLN) and prolong their action, SLNs were incorporated into thermo-responsive Poloxamer sol-gels and their fate was investigated in-vivo and in-vitro using a near infrared lipophilic fluorescent dye; dialkylcarbocyanin [1]. Leakage test, release of intact SLNs from sol-gel and SLN size and zeta potential were investigated. Biodistribution of DiR formulations (solution, free SLN and SLN-Gel) was investigated by whole-body and ex-vivo organ imaging after intraperitoneal injection in mice. SLN showed particle size of about 165 nm and a negative zeta potential of about -36 mV. Results: Leakage studies indicated that fluorescent probe does not release from SLNs. Imaging results revealed a steady profile for SLN-Gel over time, while the fluorescence intensity of solution and free SLN showed a burst followed by rapid clearance. Results also showed that SLN release occurs after gel erosion and follows a zero order profile. Conclusion: Our results indicate that NP-incorporated gel can be used to control the release of SLNs from application site and prolong their action in a sustained manner.
Keywords: solid lipid nanoparticle